THE ROLE OF INDIVIDUAL CHARACTERISTICS, PSYCHOSOCIAL ENVIRONMENTS, WORK FATIGUE, AND CALORIC ADEQUACY IN PERFORMANCE AMONG FEMALE POTTERY ARTISANS IN KARANGANYAR, BOROBUDUR - Yungki Kantiana Taqwa; Indritati Paskarini; Tri Martiana; Widarjanto; Shinta Sari Interpreter (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Pottery making is a vital tourism-supporting industry in Karanganyar, Borobudur, predominantly operated by female workers. Purpose: Investigate the factors influencing the performance of female pottery workers in Karanganyar. Method: A cross-sectional approach was employed and respondents were selected using simple random sampling techniques, yielding 43 participants out of 70 female workers. Data were collected using questionnaires and measurement devices (reaction timer, stature meter, and digital weight scale), then analyzed using Chi-square. Variables such as performance, psychosocial environment in the workplace, individual characteristics (age, marital status, number of children, and length of service), fatigue, and calorie adequacy were measured. The Copenhagen Psychosocial Questionnaire (COPSOQ) and the Individual Work Performance Questionnaire (IWPQ) were employed to assess psychosocial environments and performance, respectively. Result: The majority of pottery workers were 41 - 50 years old (32.56%), were married (93.02%), had 1 - 2 children (46.51%), and had more than 30 years of services (46.51%). Calorie deficits affected 41.86% workers, with 62.79% showing moderate performance, 81.40% experiencing a moderate psychosocial environment, and 48.84% facing mild fatigue. The Chi-square test revealed a significant association between age (p-value = 0.023), fatigue (p-value = 0.033), psychosocial environment (p-value = 0.022), and calorie adequacy (p-value = 0.047) toward performance. Conclusion: The findings highlight the importance of age, psychosocial environments, work fatigue, and calorie intake on the performance of female pottery workers.